Surface Modification of Copper Alloy by Nd: YAG Laser: An Analytical Study on Roughness Evolution and Wettability - Suleiman Elhamali; Lubna Zawi; Hussein Elmasrub; Abdulmagid Bouzed (African Journal of Advanced Pure and Applied Sciences, 2026)
Copper alloys are frequently used in a variety of industrial applications due to their high thermal and electrical conductivity. However, precise control over surface properties is required for improved performance in heat transmission, electronics, and corrosion resistance. In this study, the impact of laser treatment on a copper alloy surface irradiated by a pulsed Nd: YAG laser was investigated. The effects of laser power (10, 20, 30 W), scanning speed (100, 500, 1000 mm/s), and pulse repetition rate (10, 20, 30 kHz) on surface roughness and wettability were systematically explored. The experimental results were analyzed using the Taguchi method, which revealed that pulse repetition rate is the most critical parameter in controlling both surface roughness and wettability.